2019
DOI: 10.1002/jimd.12099
|View full text |Cite
|
Sign up to set email alerts
|

Natural history, with clinical, biochemical, and molecular characterization of classical homocystinuria in the Qatari population

Abstract: Classical homocystinuria (HCU) is the most common inborn error of metabolism in Qatar, with an incidence of 1:1800, and is caused by the Qatari founder p.R336C mutation in the CBS gene. This study describes the natural history and clinical manifestations of HCU in the Qatari population. A single center study was performed between 2016 and 2017 in 126 Qatari patients, from 82 families. Detailed clinical and biochemical data were collected, and Stanford‐Binet intelligence, quality of life and adherence to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Clinically, patients with classic homocystinuria exhibit numerous manifestations during infancy because homocysteine disrupts the development of many organ systems. These include Marfanoid habitus, pectus exavatum (curved-in sternum), pectus carinatum (protruding sternum), genu valgum, where knees are angled toward each other, and many other skeletal deformities [67,68]. In addition, ectopia lentis (dislocation of the lens) can lead to nearsightedness and blurred vision.…”
Section: Clinical Diagnosis and Disease Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, patients with classic homocystinuria exhibit numerous manifestations during infancy because homocysteine disrupts the development of many organ systems. These include Marfanoid habitus, pectus exavatum (curved-in sternum), pectus carinatum (protruding sternum), genu valgum, where knees are angled toward each other, and many other skeletal deformities [67,68]. In addition, ectopia lentis (dislocation of the lens) can lead to nearsightedness and blurred vision.…”
Section: Clinical Diagnosis and Disease Detectionmentioning
confidence: 99%
“…The early detection of homocystinuria along low protein and methionine restricted diet is the best treatment approach for all types of homocystinuria patients [68]. Referring to the homocystinuria metabolism pathway (Figure 1), the administration of folic acid and pyridoxine is also considered as an effective therapy, especially in pyridoxine-responsive patients, as these supplements have shown to enhance the CBS enzyme residual activity in more than half of the patients [77].…”
Section: Current and Potential Treatment Approachesmentioning
confidence: 99%
“…Early analyses (2012–2014) of 149 probands undergoing CES identified a causative explanation in 89 (60%) of the studied probands (Yavarna et al., ). More recent analyses of a larger cohort of >500 patients show a diagnostic yield of >48% (Al‐Dewik et al., ). This still high but slightly lower yield may involve factors such as evolving differences in variant classification techniques and guidelines as well as underlying cohort differences and practices in terms of which patients receive CES and when.…”
Section: Genetics In Qatar and The Arab Worldmentioning
confidence: 99%
“…[14] A recent study from Qatar observed that patients early diagnosed by neonatal screening had significantly higher intelligence quotient, quality of life, and adherence to treatment when compared with the late diagnosed patients. [26] In addition to the direct toxicity of Hcy on CNS, recurrent strokes can also impact cognitive skills. [11,22] Seizures occur in nearly 20% of the patients.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…[39] Good metabolic control from the neonatal period and thereafter is capable to prevent the clinical manifestations of HCU. [14,26,57,58] In late diagnosed patients, treatment can also significantly prevents morbidity and mortality. [44] Even when tHcy remained higher than the target values, a major reduction in vascular disease risk is observed in HCU patients.…”
Section: Diagnosismentioning
confidence: 99%